El consentimiento informado en el Derecho médico. Ente y Derecho en Cuba - Antúnez Sánchez, Alcides Francisco (Nómadas. Critical Journal of Social and Juridical Sciences, 2011)
In this work is intentional to state the reed to instrument inside the health system, the medical procede around informed consent institution, form medical and no medical personal that perfom conducts top atientes in all assistand institutions. Will be k,nowledge about the informed consent and what it si used in medical praxis?. This allows us to formúlate an objective: to know what an informed consent is and to identify the irregularities that concur in its and no application. We use as supporting tolos in our rsearch, specialists criteria, interview, bibliographical review, juridicial dispositions in compared law; we supported our reserac in the heuristic and axiological methods, allowing us to form a criteria respect to the analized juridicial criteria respect to the analyzed juridicial institution in this research and to arrive and know the cause that generates the problem. It is important to do an analysis inside the social context about the knowing of its conformity for medical and no medical specialists must express him its consent (verbal or written). This guides him to obtain juridical cultura and also a greater and beteer profesional ethics in medical pratice inside the social Project in Cuba.